2017
DOI: 10.1186/s12963-017-0138-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rural family physician program on child mortality rates in Iran: a time-series study

Abstract: BackgroundThe rural family physician program and social protection scheme were started in Iran about 10 years ago, and no comprehensive study has been carried out to investigate the effects of this program on mortality-related health indicators yet. The present study aims to examine the impacts of implementation of the family physician program and rural insurance program, which was launched in June 2005, on neonatal (NMR), infant (IMR), and under-5-year (U5MR) mortality rates in rural areas of Iran between 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
16
1
Order By: Relevance
“…Many studies reported the decreasing trend of such indicators after implementing similar family physician programs [23,24,40,41]. Naderi et al studied the effects of rural FP program on child mortality indicators in rural areas of Iran and reported that after the initiation of program, in 2005, the NMR and IMR decreased in comparison to the previous years, but no signi cant change was observed in U5MR [6]. Chinhoyi et al also found that FP and medical o cers supply were not signi cantly associated with the incidence of under-5 mortality [42].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported the decreasing trend of such indicators after implementing similar family physician programs [23,24,40,41]. Naderi et al studied the effects of rural FP program on child mortality indicators in rural areas of Iran and reported that after the initiation of program, in 2005, the NMR and IMR decreased in comparison to the previous years, but no signi cant change was observed in U5MR [6]. Chinhoyi et al also found that FP and medical o cers supply were not signi cantly associated with the incidence of under-5 mortality [42].…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, it was conducted in other countries including Northern Europe, Canada and a series of developing countries, which resulted in improving the e ciency of health systems and social justice [2]. The Islamic Republic of Iran (Iran), as a developing country, has already performed two signi cant health reforms during three past decades; In the mid-1980s, Primary Health Care (PHC) Network was launched in the rural regions with less than 5,000 population [6], which was signi cantly improved rural health outcomes [7]. However, the PHC services program has not obtained predominant achievements to meet the needs of population over the decades.…”
Section: Introuductionmentioning
confidence: 99%
“…Also, three important issues, including development of PHC coverage to urban and suburban areas and the PHC accessibility for care-receivers led to arising some challenges [7]. Therefore, in 2005, the FPP for rural residents was implemented [6]. In 2012, Iranian Ministry of Health and Medical Education (MoHME) also initially implemented Urban Family Physician Program (UFPP) in all provinces within the country [8].…”
Section: Introuductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2000, the promotion of maternal and child health (MCH) care through the provision of related services and recording of MCH-related indicators became a top priority for the Iranian PHC network 16 17. As of 2005, with the start of the second PHC-based reform known as Family Physician (FP) programme,18 the way each health centre (now referred to as FP team) functions within the PHC network has changed. The FP team structure was expanded to include additional staff, such as a general physician, midwives and a pharmaceutical technician 17 19–21.…”
Section: Introductionmentioning
confidence: 99%